Pemberantasan Buta Huruf Al-Qur’an pada Warga dan Komunitas Pemulung di Tempat Pembuangan Akhir Sampah (TPA) Kelurahan Karyabaru, Palembang - Sofyan Sofyan; M Hasbi; Muhammad Jhoni Nur (Universitas Mathla'ul Anwar Banten, 2020)
ERADICATING ILLITERACY OF AL-QUR'AN LETTERS ON RESIDENTS AND COMMUNITY OF SCAVENGERS AT THE FINAL WASTE DISPOSAL SITE (TPA) OF KARYABARU VILLAGE, PALEMBANG. The purpose of this community service program is to overcome literacy of the Koran in the scavenger community in the garbage dumps of Karyabaru Village, Alang-alang District, Palembang City. The method used The method used in this service is participatory action research (PAR) in the form of assistance in learning. Based on this service activity, it can be concluded that the ability of learning citizens to show an increase in writing and reading hijaiyah letters, this can be seen from the results of the evaluation at each meeting, namely: (1) the ability to write and read hijaiyah letters of learning citizens who are declared complete as many as 18 (90 %) and incomplete 2 (10%). (2) the ability to write and read changes in hijaiyah letters, namely 17 (85%) learning citizens were declared complete and 3 (15%) learning citizens were declared incomplete. (3) the ability of citizens to learn to pronounce letters correctly and fluently according to their meaning 15 (75%) learning citizens were declared complete and 5 (25%) learning residents were declared not complete, and (4) the ability of residents to learn to pronounce letters that were already marked with a long and short line according to the level in tajwid, namely there are 15 (75%) learning residents who have completed and 5 (25%) learning residents are declared incomplete.